2021
DOI: 10.1177/23328584211064305
|View full text |Cite
|
Sign up to set email alerts
|

When the Old Will No Longer Do: School and Community Practices for Student Homelessness Amid COVID-19

Abstract: In this qualitative case study, we employ 29 semistructured interviews and an array of supplemental data to explore why and how COVID-19 shaped school and community practices around student and family homelessness in Houston, Texas. Drawing on Small’s notion of organizational embeddedness, we find that COVID-19 fundamentally altered school and community practices, as educators and providers faced resource constraints, new concerns about safety, and evolving student and family needs. Providers struggled to meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…While our findings on test scores and disciplinary infractions are promising, it is important to recognize that students experiencing homelessness may still face substantial barriers to academic success, as evidenced by higher rates of dropout and lower attendance. This is a timely reminder because unfortunately, COVID-19 has only exacerbated student homelessness (Pavlakis et al, 2021). Well-coordinated antipoverty responses and community supports can help to counteract these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While our findings on test scores and disciplinary infractions are promising, it is important to recognize that students experiencing homelessness may still face substantial barriers to academic success, as evidenced by higher rates of dropout and lower attendance. This is a timely reminder because unfortunately, COVID-19 has only exacerbated student homelessness (Pavlakis et al, 2021). Well-coordinated antipoverty responses and community supports can help to counteract these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial study year is the first year where HISD residential context data were available. We excluded the year of Hurricane Harvey (2017–2018) and later years, which were disrupted by COVID-19, because both were crises of magnitude warranting separate inquiry (Pavlakis et al, 2021). In total, our sample included 400,316 students enrolled in HISD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, ESSA's newly requiring disaggregation of graduation rates by housing status and potential implications for states' McKinney-Vento funding decisions suggest policy implications in how states allocate scarce resources. Prior research on high school found that runaway youth and students experiencing homelessness specifically in the twelfth grade were relatively less likely to graduate (Aratani & Cooper, 2015;Low et al, 2017;Pavlakis et al 2020). Studies concentrating on primary and middle school students generally found that students experiencing homelessness tend to score lower on standardized tests than housed students (e.g., Cowen, 2017;De Gregorio et al, 2022).…”
mentioning
confidence: 99%